(untitled) (Bangladesh Journal of Urology, 2020)
Hydatid disease is a cyclozoonotic parasitic infestation caused by the cestodeEchinococcusgranulosus. Isolated renal involvement is extremely rare. A 58-year-old female, housewifepresented with vague abdominal pain. Ultrasonography of the abdomen revealed complexcyst arising from the right kidney. Computerized tomography scan of the abdomenrevealed large complex cyst arising from right kidney. Laparoscopic transperitonealcystectomy was performed. Isolated right renal hydatid cyst was removed in toto.Microscopic examination confirmed the diagnosis of hydatid cyst. Transperitoneallaparoscopic approach gives a better working space which helped us to remain outsideGerota’s fascia and prevent subsequent cyst rupture. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.103-105